(untitled) (American Journal of Medical Science and Innovation, 2023)
Systematic Inflammatory Response Syndrome and Sepsis are inflammatory responses to many health manifestations. Sepsis mortality is high despite global treatment standards, with metabolic resuscitation being a novel approach for managing Sepsis. The purpose of this systematic review is to assess the effectiveness of the critical care combination comprising hydrocortisone, Vitamin C, and thiamine in potentially mitigating Sepsis, reducing mortality associated with septic shock, and alleviating organ failure. In order to execute this scoping review, recent research based on the effect of vitamin C, hydrocortisone, and thiamine therapy in Sepsis and Septic Shock was identified. Data was gathered from Google Scholar, PubMed, NCBI, Hindawi, Scirp, Journal of Immunology, and Critical Care Medicine. Studies selected from different years ranging between 2017 to 2023 using keywords ‘Severe Sepsis,’ ‘Septic Shock,’ ‘Effect of Vitamin C on Sepsis, ‘Effect of Thiamine on Sepsis Treatment,’ ‘Hydrocortisone Therapy in Sepsis,’ ‘SIRS,’ ‘Septic Shock Criteria.’ Access was made to the whole texts of the articles that were found. This review could provide fundamental strategic plans dealing with specific risk factors and managing accordingly. The systemic review has been completed according to the guidelines regulated by Preferred Reporting Items for Systemic Research and Meta-Analysis. The initial search for publications on vitamin C, hydrocortisone, and thiamine in Sepsis and septic shock retrieved 1710 papers, from which 265 were selected. The reviews’ articles were further evaluated to assess vitamin C, hydrocortisone, and thiamine’s effects on Sepsis. Over 80 references were considered for their potential use in medical diagnosis and therapy. This review has included ten recent articles for the last seven years. Intravenous vitamin C, corticosteroids, hydrocortisone, and thiamine prevent organ failure, reduce vasopressor use, and decrease mortality in severe Sepsis and septic shock patients.